Antibacterial screening of epidermal mucus protein extract of freshwater Bornean spotted barb Barbodes sealei - Yang, Lee; Lim, Jia Zhen; Badiozaman, Sulaiman; Lesley Maurice, Bilung; Ngieng, Ngui Sing; Chong, Yee Ling (IAU (Tonekabon)- Iran, 2023)
The epidermal mucus of fish serves as the first line of defence against the microbe-rich aquatic environment, containing various innate immune components, including antimicrobial proteins. However, information regarding the antibacterial properties of skin mucus of Bornean native fish is scarce. This study aims to enhance the understanding of the epidermal mucus of Barbodes sealei, a Bornean endemic freshwater fish species. Pooled mucus samples were extracted using saline (aqueous extract) and acetic acid (acidic extract). The extracts were purified and concentrated through ammonium sulfate precipitation. This study presents the antibacterial screening of these mucus extracts against 16 selected bacterial strains. The results revealed that among the bacterial strains tested, only Salmonella braenderup ATCC BAA 664 showed sensitivity to the acidic extracts, while none of the aqueous extracts exhibited any antibacterial activity. The findings suggest that higher protein contents in the extracts did not necessarily correlate with better antibacterial activities. To identify the major proteins present in the active extracts and determine the antibacterial proteins, a qualitative bioanalysis was conducted using high-throughput Liquid Chromatography with Tandem Mass Spectrometry (LC-MS/MS). Four antibacterial proteins, namely Histone H2A, Histone H2B, Histone H4, and Heat shock protein 70, were identified based on comparison with existing literature. Further isolation and characterisation of the active components, particularly the antimicrobial proteins, are warranted to gain deeper insight into their role in fish immunity. This study establishes the antibacterial potential of epidermal mucus from B. sealei and proposes it as a non-invasive source for the isolation of new biologically active compounds, such as antimicrobial proteins and peptides.